2013
DOI: 10.1007/s11064-013-0992-5
|View full text |Cite
|
Sign up to set email alerts
|

Ethylenedioxy-PIP2 Oxalate Reduces Ganglioside Storage in Juvenile Sandhoff Disease Mice

Abstract: Sandhoff disease is an incurable neurodegenerative disorder caused by mutations in the lysosomal hydrolase β-hexosaminidase. Deficiency in this enzyme leads to excessive accumulation of ganglioside GM2 and its asialo derivative, GA2, in brain and visceral tissues. Small molecule inhibitors of ceramide-specific glucosyltransferase, the first committed step in ganglioside biosynthesis, reduce storage of GM2 and GA2. Limited brain access or adverse effects have hampered the therapeutic efficacy of the clinically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…A signifi cant reduction in ganglioside GM2 and GA2 was observed in the cerebrums and cerebellums of the mice, a response not observed with eliglustat ( 54 ). These data support the view that PDMP-based homologs can be designed to lower GSLs within the CNS.…”
Section: Downloaded Fromsupporting
confidence: 70%
“…A signifi cant reduction in ganglioside GM2 and GA2 was observed in the cerebrums and cerebellums of the mice, a response not observed with eliglustat ( 54 ). These data support the view that PDMP-based homologs can be designed to lower GSLs within the CNS.…”
Section: Downloaded Fromsupporting
confidence: 70%
“…To address this possibility, we analyzed BMP levels in young Hex ␤ ( Ϫ / Ϫ ) mice at p15, well before the onset of behavioral symptoms and infl ammation. However, GM2 ganglioside storage is observable in the p15 Hex ␤ ( Ϫ / Ϫ ) mice ( 58 ). We found that brain levels of BMP were higher in the p15 Hex ␤ ( Ϫ / Ϫ ) mice than in the normal age-matched controls.…”
Section: Discussionmentioning
confidence: 59%
“…In our BMP storage was observed in the livers of SD mice ( Table 1 ), where N-glycolylneuraminic acid-GM2 is also stored ( 58 ). This observation indicates that BMP co-accumulates with ganglioside storage, rather than as a downstream by-product of a nonfunctional enzyme.…”
Section: Bmp Separates From Its Structural Isomer Pg By Hptlc and Masmentioning
confidence: 49%
See 1 more Smart Citation
“…Although anecdotal reports in individual patients suggest an impact on neurological manifestations in type 3 GD, a controlled clinical trial involving 25 subjects over a two year time course failed to demonstrate effectiveness on neurological endpoints such as saccadic eye movements ( 28 ). However, newer small molecule modulators with the potential to gain access to the CNS and impact glycolipid metabolism are now emerging (29)(30)(31)(32).…”
Section: Approaches To Therapeutic Interventionmentioning
confidence: 99%